In vitro fertilization and embryo transfer in Pretoria - van der Merwe, J V; Irsigler, U M; de Milander, C; Wimmers, M S; Botes, A D; Snyman, E; von Prince, M S; Koch, Z; Hurter, P (South African medical journal, 1984)
Details of the in vitro fertilization and embryo transfer programme at the Department of Obstetrics and Gynaecology of the H. F. Verwoerd Hospital and the University of Pretoria are presented. From 1 March 1982 to 30 November 1983, 67 cycles in 47 patients were induced using clomiphene citrate and human chorionic gonadotrophin (hCG) (46 patients) and human postmenopausal gonadotrophin/hCG (1 patient). In 5 patients ovum recovery was unsuccessful owing to severe adhesions. In the remaining 42 patients 59 oocyte recoveries out of a total of 62 attempts were successful, a 95% recovery rate. One hundred and seventy-nine ova were recovered (2,9 per laparoscopy), of which 143 (80%) were viable. Forty-six per cent of fertilized ova cleaved actively. Forty-one transfers of 66 embryos (average 1,6 embryos per transfer) resulted in 5 pregnancies (12% pregnancy rate per transfer). Three preclinical pregnancies aborted spontaneously. Two pregnancies are ongoing at 30 and 32 weeks' gestation. Thus, the programme has so far led to 2 third-trimester pregnancies. Consolidation and refinement of techniques should lead to a steady increase in success at this centre.